Urban size and senior executive compensation: Evidence from China - Jiafeng Zong; Man Guo; Liang Zhou (Journal of Urban Management, 2019)
Relying on data of Chinese listed companies and city scale during 2005-2010, we document a positive relationship between the size and location of urban firms and total senior executive compensation. Tenure and corporate performance have a positive impact on the total senior executive compensation in mega-cities and large cities. Higher wages in big cities may be compensating for the price of housing and price of city amenity. This conclusion may explain why people, especially senior executives, are heading to big cities.
Keywords: L20; R13; R23; R38; 710; Agglomeration; Senior executive compensation; Wage premium